Lie Groupoids and Generalized Contact Manifolds - Fulya Şahin (Abstract and Applied Analysis)
We investigate relationships between Lie groupoids and generalized almost contact manifolds. We first relate the notions of integrable Jacobi pairs and contact groupoids on generalized contact manifolds, and then we show that there is a one to one correspondence between linear operators and multiplicative forms satisfying Hitchin pair. Finally, we find equivalent conditions among the integrability conditions of generalized almost contact manifolds, the condition of compatibility of source, and target maps of contact groupoids with contact form and generalized contact maps.